THE CORRELATION AMONG TEXT READABILITY, READING STRATEGY AND READING COMPREHENSION - Lailatul Isnaini (Language-Edu, 2021)
This investigation explores the correlation among readability, learners' reading strategy and reading comprehension that was completed with 96 secondary school 10th grade students who received two kinds of reading comprehension tests, early of them including the simpler readability level content, and the subsequent one is the troublesome. The two of them were joined by a survey on reading strategy they utilized. This study discovered five unique results and was also aligned with the question posed. The first outcome was centered on the measure level of text readability of English textbook which has 4 levels. Secondly, this study found the most frequently reading strategies used by students are problem solving reading strategies (PROB) and support reading strategies (SUP). Third, the result of this investigation revealed that there is correlation between text readability and reading comprehension (rxy =־0.345), however the coefficient is negative. Secondly, there is correlation (rxy = 0.254) between text readability and reading strategy and the coefficient is positive. Finally, there is also positive correlation (rxy= 0.434) between reading strategy and reading comprehension. These outcomes implicated that the teacher should consider the readability level of text used as teaching material and familiarize reading strategies to their students let they have good reading skill.